Techno Economic Analysis of Offshore Wind Turbine in Kudat, Sabah Malaysia - Palaniappan, Pavitirakumar (Universiti Teknologi PETRONAS, 2020)
This paper focuses on the analysis of the techno economic for wind turbine platform at offshore Kudat, Sabah. Kudat is identified as the most suitable location to install wind turbines as the Kudat offshore has the highest wind speed in offshore Malaysia. The Government of Malaysia has set a striving target to achieve higher usage of renewable energy (RE) in the Malaysian energy mix. Malaysia currently has approximately 2% of its electricity from RE generation sources compared to the total generation mix and has a 20% penetration goals by 2025. This techno economic analysis is conducted to identify all the cost for installation, operation, and maintenance of wind turbines. This research mainly focusses on collecting the wind speed data and identifying the amount of energy that can be generated by a wind turbine per annum. This paper covers in depth the economic analysis of wind turbine such as cash outflow and cash inflow throughout its lifetime which is 25 years.